Fano-like anti-resonances in strongly coupled binary Coulomb systems. (January 2015) - Silvestri, L.; Kalman, G. J.; Donkó, Z.; Hartmann, P.; Kählert, H.
Abstract Molecular-dynamics (MD) simulations of a strongly coupled binary ionic mixture have revealed the appearance of sharp minima in the species-resolved dynamical density fluctuation spectra. This phenomenon is reminiscent of the well-known Fano anti-resonance, occurring in various physical processes. We give a theoretical analysis using the quasi-localized charge approximation, and demonstrate that the observed phenomenon in the equilibrium spectrum is a novel manifestation of the Fano mechanism, that occurs at characteristic frequencies of the system different from the conventional classical Fano frequencies.